Women Leaders of Nations - Nardo, Don; 1947- (San Diego, CA, 1999)
Discusses some notable female leaders of history, including Cleopatra, Queen Victoria, and Golda Meir.
Includes bibliographical references and index.
Keywords: Heads of state; Kings, queens, rulers, etc; Juvenile literature; Leadership; Women; Women in politics; Biography; Heads of state; Biography; Biography